Isolation And Identification Of Some Pathogenic Bacteria And Fungi From Restaurantes And Meat Shop’s In Al-Samawa City - Yaseen, Hasanain Marzoq (University of Thi-Qar Journal of Science, 2019)
The present study include isolation and identification of some pathogenic fungi and bacteria from restaurant and meat shop’s in AL-Samawa city by taking samples from 15 restaurants and 15 meat shop’s, choose randomly with three replicates for each sample on solid culture medium Potato’s Dextrose Agar (PDA) for fungi and Nutrient Agar for bacteria. The results showed several fungal and bacterial species were isolated from these places, for restaurants fungal species were: Rhizopus stolanifer, Penicillium notatum, Fusarium oxysporum, Alternaria alternata, Aspergillus niger, Rhizoctonia solani, Cladosporium sp. and Aspergillus flavus, with percentage of frequency which has (21.78, 10.89, 7.92, 8.91, 18.81, 7.92, 6.93 and 16.83)% respectively, while the bacterial species were: Bacillus cereus, Clostridium botulinum , Escherichia coli, Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus and Lactobacillus subtilus (12.16, 9.45, 21.62, 18.91, 16.21, 12.16 and 9.45)% respectively. From meat shop’s the isolated fungal species were: Aspergillus niger, Penicillium notatum, Aspergillus flavus, Rhizopus stolanifer and Cladosporium sp. (23.91, 16.30, 19.56, 28.26 and 11.95)% respectively, while the isolated bacterial species were: Salmonella typhi, Staphylococcus aureus ,Lactobacillus subtilus, Pseudomonas aeruginosa, Escherichia coli and Clostridium perfringens (15.87, 19.04, 17.46, 9.52, 23.80 and 14.28)% respectively.